Comparing visual and objective skin assessment with pressure injury risk. Issue 4 (15th July 2015) - Borzdynski, Caroline J; McGuiness, William; Miller, Charne
Abstract: Contemporary approaches to pressure injury (PI) risk identification rely on the use of risk assessment tools and visual skin assessment. Objective biophysical measures that assess skin hydration, melanin, erythema and lipids have not been traditionally used in PI risk; however, these may prove useful as a risk assessment tool. The relationship between subjective visual assessments of skin condition, biophysical measures and PI risk warrants investigation. This study used a descriptive correlational design to examine the relationship between measures of skin hydration, colour (melanin and erythema) and lipids at PI‐prone areas amongst geriatric persons ( n = 38), obtained using biophysical skin measures and visual skin assessment. Twice daily measures of epidermal hydration, colour and lipids were assessed using the SD202 Skin Diagnostic (Courage + Khazaka GmBH, Cologne, Germany) over pressure‐prone areas of the body of study participants over seven consecutive days. Concurrent visual assessment of skin hydration and colour was performed. Results obtained using the SD202 Skin Diagnostic were compared with results gathered from visual assessment and examined for their association with participants' PI risk based on scores of the Norton Risk Assessment Scale. While epidermal hydration and skin colour reading scores did not vary significantly over the data collection period, lipid readings could not be registered on any occasion. With the exception of skin dryness, skin parameters via both objective and subjective means had significant, positive correlations. Statistically significant correlations emerged between visual assessment of skin wetness at the sacrum ( r = −0·441, P < 0·01) and ischia ( r = −0·468, P < 0·01) and Norton Risk Assessment Scale scores. It was found that the objective assessment of epidermal hydration (skin wetness) was also significantly associated with PI risk at the sacrum ( r = −0·528, P < 0·01), as well as the right ischia ( r = −0·410, P < 0·05) and left ischia ( r = −0·407, P < 0·05). Erythema, when assessed objectively, was significantly correlated with PI risk at the sacrum ( r = −0·322, P < 0·05). Such findings indicating that the finer measures afforded by the SD202 Skin Diagnostic in the assessment of the subtle red hues displayed in erythematous skin may provide an additional advantage over traditional, clinician assessment.